1993
DOI: 10.1177/000348949310200806
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Otitis Media with Effusion Induced by Platelet Activating Factor

Abstract: This study tested the hypothesis that platelet activating factor (PAF) in the middle ear can induce otitis media with effusion (OME) and that PAF antagonists can prevent PAF-induced OME. An initial trial of 16 micrograms of PAF was injected into chinchilla bullae, and all ears developed middle ear effusion (MEE) within 48 hours. Subsequent trials were performed to test dose dependency. Interestingly, 1 or 16 micrograms of PAF caused more MEE and inflammation than did 4 or 8 micrograms. A dose of 0.5 micrograms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 13 publications
1
44
0
Order By: Relevance
“…All animals inoculated with formalin-killed H. influenzae in the control group developed MEE within 6 h of inoculation [11,15]. WEB-2170 has shown to prevent PAF induced OME effectively when it was administered intraperitoneally [11], and inhibited the PAF-induced mucous glycoprotein secretion [7,13]. SCH-37224 was developed as an anti-allergic agent that inhibits the formation of LTs and thromboxane release in vitro and in vivo [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All animals inoculated with formalin-killed H. influenzae in the control group developed MEE within 6 h of inoculation [11,15]. WEB-2170 has shown to prevent PAF induced OME effectively when it was administered intraperitoneally [11], and inhibited the PAF-induced mucous glycoprotein secretion [7,13]. SCH-37224 was developed as an anti-allergic agent that inhibits the formation of LTs and thromboxane release in vitro and in vivo [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Previously in our lab, metabolites of AA and PAF have been identified in human MEE as well as in experimentally induced middle ear effusions in animals [2,7,9,10]. LTs and PAF seem to be more pro-inflammatory than PGs, according to our previous animal studies [6,7,10]. LTC 4 , LTD 4 , and LTE 4 are called cystein LTs (CysLTs).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Minami et al [6] reported that PAF, at concentrations over 10 -9 M, led to dysfunction of the eustachian tube, and Ganbo et al [5] found that PAF dose dependently inhibited mucociliary transport activity in the eustachian tube in vitro. In 1993, Rhee et al [2] reported that the injection of PAF into the middle ear of chinchillas with an intact eustachian tube induced COME and that PAF antagonists effectively prevented PAF-induced COME. Lin et al [3,4] reported that PAF induced excessive secretion of mucous glycoprotein in cultured chinchilla middle ear epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…PAF is one of the most potent lipid mediators known and has a wide variety of physiological and pathophysiological actions [1]. PAF seems to play a major role in the production of middle ear effusion (MEE), as a result of increased vascular permeability [2], and stimulating epithelial secretory activity [3,4]. PAF also reduces the mucociliary activity on the middle ear [5] and causes eustachian tube dysfunction [6].…”
Section: Introductionmentioning
confidence: 99%